Mountain roads and non‐native species modify elevational patterns of plant diversity. Issue 6 (13th March 2018) - Haider, Sylvia; Kueffer, Christoph; Bruelheide, Helge; Seipel, Tim; Alexander, Jake M.; Rew, Lisa J.; Arévalo, José Ramón; Cavieres, Lohengrin A.; McDougall, Keith L.; Milbau, Ann; Naylor, Bridgett J.; Speziale, Karina; et al.
Abstract: Aim: We investigated patterns of species richness and community dissimilarity along elevation gradients using globally replicated, standardized surveys of vascular plants. We asked how these patterns of diversity are influenced by anthropogenic pressures (road construction and non‐native species). Location: Global. Time period: 2008–2015. Major taxa studied: Vascular plants. Methods: Native and non‐native vascular plant species were recorded in 943 plots along 25 elevation gradients, in nine mountain regions, on four continents. Sampling took place in plots along and away from roads. We analysed the effects of elevation and distance from road on species richness patterns and community dissimilarity (beta‐diversity), and assessed how non‐native species modified such elevational diversity patterns. Results: Globally, native and total species richness showed a unimodal relationship with elevation that peaked at lower‐mid elevations, but these patterns were altered along roads and due to non‐native species. Differences in elevational species richness patterns between regions disappeared along roadsides, and non‐native species changed the patterns' character in all study regions. Community dissimilarity was reduced along roadsides and through non‐native species. We also found a significant elevational decay of beta‐diversity, which however was not affected by roads or non‐native species. Main conclusions: Idiosyncratic native species richness patterns in plots away from roads implicate region‐specific mechanisms underlying these patterns. However, along roadsides a clearer elevational signal emerged and species richness mostly peaked at mid‐elevations. We conclude that both roads and non‐native species lead to a homogenization of species richness patterns and plant communities in mountains.